Electrical properties of materials - Solymar, L. (Laszlo); Walsh, D. (Donald) (Oxford ; Oxford University Press, 2010)
This work offers a simple treatment of the relevant mathematics and a clear guide to applications for students in electrical and electronic engineering. The fundamental ideas relevant to the understanding of the electrical properties of materials are emphasized.
Includes bibliographical p. [430-431] and index.
Description based on print version record.
Keywords: Solids -- Electric properties; Materials -- Electric properties; Energy-band theory of solids; Free electron theory of metals